2016
DOI: 10.1002/minf.201600008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations Bring New Insights into Protoporphyrinogen IX Oxidase/Protoporphyrinogen IX Interaction Modes

Abstract: Protoporphyrinogen IX oxidase (PPO, EC 1.3.3.4) catalyzes the oxidation of protoporphyrinogen IX (protogen IX) to protoporphyrin IX (proto IX) in the haem/chlorophyll biosynthetic pathway. Although extensive studies of PPO have already afforded many insights into its biological function and its significance to agriculture and medicine, details of the enzymatic mechanism as well as the nature of the specific amino acids involved in substrate binding still remain largely unknown due to the lack of structural inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Protoporphyrinogen IX oxidase (PPO, EC 1.3.3.4) is the penultimate enzyme in the biosynthetic pathways of heme and chlorophyll. In the presence of O 2 , PPO catalyzes the aromatization of colorless protoporphyrinogen IX to deeply colored protoporphyrin IX. Under normal conditions, the product protoporphyrin IX is directly captured by the downstream Mg-chelatase without leaking out to the surrounding medium . PPO-inhibiting herbicides can prevent the binding of the substrate protoporphyrinogen IX to the active site of PPO, which, in turn, results in the accumulation of protoporphyrinogen IX in the cytoplasm. , After an auto-oxidation process, the substrate is converted to the photosensitizing protoporphyrin IX, which would generate high levels of reactive oxygen species under sunlight and cause cell membrane lipid peroxidation. Commercial PPO herbicides have many advantages, including a broad range of weed control and low usage rates. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protoporphyrinogen IX oxidase (PPO, EC 1.3.3.4) is the penultimate enzyme in the biosynthetic pathways of heme and chlorophyll. In the presence of O 2 , PPO catalyzes the aromatization of colorless protoporphyrinogen IX to deeply colored protoporphyrin IX. Under normal conditions, the product protoporphyrin IX is directly captured by the downstream Mg-chelatase without leaking out to the surrounding medium . PPO-inhibiting herbicides can prevent the binding of the substrate protoporphyrinogen IX to the active site of PPO, which, in turn, results in the accumulation of protoporphyrinogen IX in the cytoplasm. , After an auto-oxidation process, the substrate is converted to the photosensitizing protoporphyrin IX, which would generate high levels of reactive oxygen species under sunlight and cause cell membrane lipid peroxidation. Commercial PPO herbicides have many advantages, including a broad range of weed control and low usage rates. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…There are two isoforms of PPO in plants: one is plastidic PPO1 and another is mitochondrial PPO2 . It was found that the catalytic domains of PPO2 in different plants are highly conserved. ,,, Therefore, analyzing the binding modes of representative PPO inhibitors with PPO could provide insights for further design and optimization of PPO inhibitors with improved performance. In 2004, Koch et al determined the crystal structure of Nicotiana tabacum PPO2 (NtPPO) in complex with a PPO inhibitor 4-bromo-3-(5-carboxy-4-chloro-2-fluoro-phenyl)-1-methyl-5-trifluoromethyl-pyrazol (INH) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, different types of PPO inhibitors have conflicting structure–activity relationships. The possible reason may be that these compounds are competitive inhibitors, and their structures can overlay with two or three pyrrole rings of protoporphyrinogen IX. In 2004, Koch et al reported the crystal structure of Nicotiana tabacum PPO (NtPPO) in complex with a phenylpyrazole-type inhibitor 4-Bromo-3-(5′-carboxy-4′-chloro-2′-fluoro-phenyl)-1-methyl-5-trifluoromethyl-pyrazol (INH) . They found that INH can mimic half of the structure of protoporphyrinogen IX upon binding to the active site.…”
Section: Introductionmentioning
confidence: 99%
“…Protoporphyrinogen oxidase (PPO) is the last common enzyme in both chlorophyll (in plants) and haem (in animals) biosynthesis [1,2,3,4], catalyzing the oxidation of protoporphyrinogen IX to protoporphyrin IX via molecular oxygen [5,6,7,8,9], and this enzyme has been identified as one of the most significant targets for herbicide research [10,11]. During the last thirty years, a number of active compounds inhibiting the enzyme PPO have been synthesized [12,13], some of which have been developed for use as low-toxicity, efficient, broad-spectrum commercial herbicides [14,15], such as Flumioxazin [16,17], sulfentrazone [18] and saflufenacil [19].…”
Section: Introductionmentioning
confidence: 99%